A NEW APPROACH TO SYNTHESIS METHACRYLIC MONOMERS N-ALKYLMETHACRYLAMIDE USING AN ECOLOGIC AND FRIENDLY CATALYST MAGHNITE H - Derkaoui, S; Belbachir, M (university of el oued/جامعة الوادي, 2019)
In this paper, we have developed a novel procedure to synthesize four monomers formulated as 1,4-bis(Methacryloyl)Piperazine, N-Methacryloylmorpholine, N-Phenylmethacrylamide and N-Formyldimethacrylamide. N-Alkylmethacrylamide monomers are synthesized by the condensation of primary amine aniline and formamide or heterocyclic secondary amines such as piperazine and morpholine with methacrylic anhydride using an ecologic and friendly catalyst “Maghnite H +” , a proton exchanged montmorillonite clay by replacing a toxic reactant acryloyl chloride and triethylamine which are using in previously published studies. This new approach is even more interesting since this synthesis is carried out in bulk (without solvent) and at 0 °C for 2 hours, obtaining a better yield around 70% and selectivity to the product 100%. These monomers are characterized and confirmed by Infrared Spectroscopy (FTIR), 1 H and 13C nuclear magnetic resonance (NMR) spectroscopy
Article
Keywords: Green chemistry; Montmorillonite clay; N-Alkylmethacrylamide; One-pot synthesis; Methacrylic anhydride.